Grobmotorische Fähigkeiten bei Kindern mit Zerebralparese und geistiger Behinderung - Djuric-Zdravkovic, Aleksandra; Perovic, Dijana; Milanovic-Dobrota, Biljana; Japundza-Milisavljevic, Mirjana (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2020)
Objectives The aim of this study is to determine the connection of gross motor skills (locomotor skills and object control) and the degree of associated intellectual disability (ID) in children with cerebral palsy (CP).Participants and methods The study sample included 54 children with CP and associated ID age 5 years to 6 years and 11 months. For the assessment of tested skills, The Gross Motor Function Classification System-Expanded and Revised (GMFCS-E&R), Wechsler Preschool and Primary Scale of Intelligence-Fourth Edition (WPPSI-IV) and Test of Gross Motor Development Second Edition (TGMD-2) were used.Results The results of this study indicate better quality of locomotor skills than object control skills in children with CP and associated ID. Children with CP and mild ID have better quality of locomotor skills and object control, than children with CP and moderate ID. Differences between these 2 groups of children are presented relative to GMFCS-E&R levels.Conclusion This study has determined significant interconnection of the quality of gross motor functions and intellectual capacity in preschool children with CP. This should be considered when creating more detailed individual developmental rehabilitation plan in children with CP and associated ID and predict adequate measures of developmental stimulation.
Keywords: Locomotor skills; object control; cerebral paralysis; intellectual disability